(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
In the article, from the unified positions of the theory of relativity, physical processes are generalized that occur synchronously in the space of inertial coordinate systems in the entire range of possible movements – from the observed movements of celestial bodies to intra-atomic interactions of electromagnetic fields and quantum particles. Atomic objects manifest and fixed by direct detection of elastic wave interactions on a pulsar time scale in their natural states, excluding particle collisions. In the inertial frame, the body moves according to the Kepler-Newton laws (inertiality in the usual mechanical sense). During the passage of the wave front, the electromagnetic field of the pulsar, interacting with the electromagnetic field of microparticles, fixes their discrete mechanical states on its scale with an accuracy of up to a quantum of time allowed by the pulsar scale. The discrete mechanical states of microparticles measured on the pulsar scale are multiples of the constant value ∂T = 5.551115123125780E-17s, they are repeated in any inertial coordinate system. Their number is finite, regardless of the duration of the measurements.